Daya Gabung Beberapa Varietas Padi (Oryza sativa L.) pada Persilangan Dialel Menggunakan Metode Griffing II - Anak Agung Ketut Sudharmawan; Baiq Erna Listiana; Sofi Rianti (LPPM Universitas Mataram, 2021)
Diallel crossing is a method that is widely used to determine the ability to combine each individual so that it can identify the potential elders to be used in crossbreeding programs to assemble high yielding varieties. This experiment aims to determine the combining power of dialelic crosses of several varieties of rice using the Griffing II method, carried out in the experimental field of the Faculty of Agriculture, Mataram University in Nyiur Lembang Village, Narmada District, West Lombok Regency, from February to July 2019. This experiment uses the method experiments carried out in the field. The materials used in this experiment were four parents, namely IPB 3S variety, Situ Patenggang variety, Inpari 32 and G11 strain and the phenotype of the cross between the four parents. The experimental results showed that the effects of general affinity and special affinity for all observed characters (plant height, number of productive tillers, number of non-productive tillers, panicle length, number of filled grain, number of empty grain and weight of 100 grains) were significantly different, except on the effect of general affinity for the number of non-productive tillers showed no significant difference. The results of the combined power analysis of the four elders were positive, so it can be said that the four elders would get good results when crossed with a number of other genotypes.